The Effectiveness of a 4-Week Physical Exercise Program in Patients with Pulmonary Arterial Hypertension: A Pilot Study in Sumatra - Kiki Krevani, Citra; Azzuhdi, Muhammad Zakiy; Soegistiono, Feiky Herfandi; Maulina, Putri (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2024)
Background: Pulmonary Arterial Hypertension (PAH) is known to induce a decline in functional capacity, attributed to mechanisms such as right ventricular dysfunction, chronotropic incompetence, ventilation abnormalities, and skeletal muscle dysfunction. Despite the recommendation of physical exercise programs, a standardized and easily implementable regimen for PAH patients is currently lacking. This study aims to investigate the influence of physical exercise on the 6-minute walking distance (6MWD), functional capacity, and pulmonary vascular resistance (PVR) in individuals with PAH. Methods: This study employed a non-randomized clinical trial design involving adult patients with Pulmonary Arterial Hypertension (PAH), who were divided into intervention and control groups. Baseline characteristics, differences in 6-Minute Walking Distance (6MWD), peak VO2, and Pulmonary Vascular Resistance (PVR) before and after a four-week period (20 sessions, five times a week) of physical exercise were documented. The Shapiro-Wilk normality test was conducted before analyzing numerical data, followed by independent t-tests or Mann-Whitney tests to assess intergroup differences. Results: The study included 32 PAH patients, with 16 subjects in each group. Baseline characteristics revealed a distribution of 22 females (68.75%) and 10 males (31.25%), with an age range of 18-55 years. Statistical analysis indicated no significant differences in baseline characteristics, hemodynamic data, and echocardiography between the two groups. However, there were significant differences between the control and intervention groups in terms of Δ6MWD (17.07 ± 48.30 (95% CI: -10.82 – 44.96) vs. 115.36 ± 54.69 meters (95% CI: 83.78 – 146.94), p-value < 0.001), ΔVO2 peak (159.42 ± 209.32 (95% CI: -92 – 707) vs. 14.5 ± 60.4 (95% CI: -77 – 148), p-value < 0.05), and ΔPVR (-1.36±0.67 (95% CI: -0.33-(-2.85)) vs. -0.34±0.30 (95% CI: -0.39-(0.63)), p-value < 0.05). Conclusion: A four-week physical exercise program improved 6MWD, functional capacity, and PVR in patients with PAH.